Implementasi teori belajar konstruktivisme dalam pembelajaran sains - Sugrah, Nurfatimah Ugha (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2019)
Constructivism learning theory is a theory that gives freedom to humans who want to learn or look for their needs with the ability to find their wants or needs with the help of others, so this theory provides activeness for humans to learn to find their own competencies, knowledge, or technology and other things that needed to develop itself. Constructivism learning theory holds that people produce knowledge and form meaning based on their experiences. In constructivism, learning is represented as a constructive process in which students build internal illustrations of knowledge, interpretations of personal experiences. Constructivism teaching is based on learning that occurs through the active involvement of students in the construction of meaning and knowledge. Teaching science from a constructivist perspective aims to give students knowledge of science in such a way that they not only understand the concepts and principles of science, but also the significance of science learning. The emphasis on constructivism and direct inquiry-oriented learning to promote children's conceptual knowledge by building on previous understanding, active involvement with subject content, and applications for real-world situations has been. A constructivist view emphasizes discovery, experimentation, and open problems. Teori belajar konstruktivisme adalah sebuah teori yang memberikan kebebasan terhadap manusia yang ingin belajar atau mencari kebutuhannya dengan kemampuan menemukan keinginan atau kebutuhannya tersebut dengan bantuan orang lain, sehingga teori ini memberikan keaktifan terhadap manusia untuk belajar menemukan sendiri kompetensi, pengetahuan, atau teknologi dan hal lain yang diperlukan guna mengembangkan dirinya sendiri. Teori pembelajaran konstruktivisme berpendapat bahwa orang menghasilkan pengetahuan dan membentuk makna berdasarkan pengalaman mereka. Dalam konstruktivisme, pembelajaran direpresentasikan sebagai proses konstruktif di mana pelajar membangun ilustrasi internal pengetahuan, interpretasi pengalaman pribadi. Pengajaran konstruktivisme didasarkan pada pembelajaran yang terjadi melalui keterlibatan aktif siswa dalam konstruksi makna dan pengetahuan. Pengajaran sains dari perspektif konstruktivisme bertujuan untuk memberikan siswa pengetahuan sains sedemikian rupa sehingga mereka tidak hanya memahami konsep dan prinsip sains, tetapi juga signifikansi dari pembelajaran sains.